New Approaches for Post-Surgical Treatment of Glioblastoma: Targeting GLI-Similar (GLIS) Genes with Stimuli-Responsive Polymer/RNA Complexes - Gumus, Nurcan (2024)
Glioblastoma is the deadliest type of brain tumour, and many therapy approaches have been applied to increase the median life expectancy. However, clinical outcomes have not improved, and innovative glioblastoma treatments are needed. Targeting GLI1-3 and GLI-associated genes (GLIPR1 and GLIS1-3 gene family), which contribute to glioblastoma pathogenesis by controlling apoptosis, proliferation, and migration, would be a promising cancer treatment. Small interfering RNA (siRNA) therapeutics are considered the best way to downregulate these genes, as they can suppress the expression of any gene at the mRNA level with negligible toxicity. However, siRNA delivery is one of the issues impeding the clinical applications of siRNA therapy owing to short half-life in circulation and poor membrane penetration. Nonviral polymer-carriers, including cationic polymers, play a key role in addressing these challenges. The local delivery approach in glioblastoma has garnered interest in enhancing therapy efficacy and preventing tumour recurrence by facilitating high therapeutic accumulation and directly targeting residual tumour cells. Out of the local treatment approaches, thermosensitive and injectable hydrogels, including poly(ethylene glycol)-poly(ε-caprolactone)-poly(ethylene glycol) (PECE), are attracting significant interest due to application into a target area and the ability to spread evenly to the irregular edges of the postoperative cavity. The primary objectives of this thesis are to design and synthesise cationic polymer delivery systems for siRNA oligonucleotides, to identify target genes that would have therapeutic effects on glioblastoma and to incorporate these siRNA-polyplex systems with a thermosensitive hydrogel to enhance post-surgery siRNA delivery for therapy. Chapter 2 details the generation of a polymer library, including linear and branched poly(amido amine) cationic polymers. These cationic polymer backbones were derived from CBA (NN’-Cystamine Bisacrylamide) and contained N-Boc-1,4-diaminobutane (N.Boc DAB) and/or 4-amino-1-butanol (ABOL) pendant groups (depending on polymer topology), and polymer branching was controlled by using 1,4-diaminobutane (DAB), Tris(2-aminoethyl)amine (TAEA), and 1,3,5-Triacryloylhexahydro-1,3,5-triazine (TAHTA) moieties. These PAAs polymers are biodegradable, and from the set of materials synthesised, the HO-(pCBA-ABOL-TAHTA10%)-OH polymer demonstrated the best transfection efficiency, cellular uptake, and penetrating ability in both monolayer and spheroid cell models of glioblastoma cells. Chapter 3 details the assessment of the expression profile of GLI1-3 and GLI-associated genes using RNAseq, qRT-PCR and genomic data analysis on the R2 website. Demonstrating the highest mRNA expression level in glioblastoma cells, the GLIS2 and GLIS3 genes were identified as target genes to investigate their potential involvement in the pathogenesis of glioblastoma. In patient-derived glioblastoma cells, siRNA suppression of the GLIS2 and GLIS3 genes induced apoptosis, reduced cell metabolic activity, and the number of invaded glioblastoma cells. Co-administration of GLIS2.1 and GLIS3.1 siRNA pairings was more effective at regulating the biological effects of target genes in glioblastoma cells than the single dosage of each siRNA. Chapter 4 details designing a local delivery system for postoperative treatment of glioblastoma. For this purpose, a polyplex+PECE hydrogel was developed by loading HO-(pCBA-ABOL-TAHTA10%)-OH-siRNA complexes into PECE thermosensitive hydrogel. In vitro and ex vivo studies demonstrated that the polyplex+PECE hydrogel enabled a sustained siRNA release, resulting in a prolonged silencing effect and a gradual diffusion into the tissue. Overall, the results from this thesis reveal that HO-(pCBA-ABOL-TAHTA10%)-OH-siRNA is a promising carrier for siRNA delivery, and that GLIS2 and GLIS3 genes are potential therapeutic targets for glioblastoma. Administering the polyplexes-siRNA+PECE hydrogel into the tumour resection cavity may increase the efficacy of glioblastoma therapy. To our knowledge, this is the first study that used these specific cationic polymers and evaluated the effects of GLIS2 genes in glioblastoma cells.